Growth performance of Shorea materialis under Pterocymbium javanicum as a shade provider - Zakaria, Murdani (2016)
Shorea materialis is the one of critically endangered species in a world. A trial plantation conducted at Ragut 3, Ladang Puchong, Universiti Putra Malaysia, Selangor to evaluate the growth performance of Shorea materialis under the line-planted Pterocymbium javanicum at Ragut 3, Ladang Pertanian Puchong, Universiti Putra Malaysia. This study was conducted for a four-month period of which tree diameter, leaf area, number of leaves, and total height are recorded. In addition, light intensity, relative humidity and temperature were recorded during morning, midday and evening to evaluate the environmental factors that may affect the growth performance. Based on the independent sample T-test result, the (p>0.05) for growth parameters of S. materialis for both Block 1 and Block 2 shows there is no significant different between blocks. Therefore, S. materialis has a potential to introduce in different habitat for conservation based on the growth performance in two blocks that has been planted under the P. Javanicum, but this study also should be prolonging to get the further and actual information about this species.